Analisis Portofolio Optimal Dengan Model Markowitz Sebagai Dasar Keputusan Investasi Studi Kasus Pada Saham Indeks Investor 33 Yang Terdaftar di BEI Tahun 2022-2023 - Ilham Ardiansyah; Zufrizal Zufrizal; Jalilah Ilmiha (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
This research aims to analyze the optimal portfolio using the Markowitz model on the INVESTOR33 stock index during the 2022-2023 period, to identify the best stock combination that maximizes returns and minimizes risks according to investor risk profiles. The research employs a descriptive quantitative method, analyzing historical stock price data from 30 sample companies to construct the optimal portfolio. The results show that seven stocks meet the criteria for an optimal portfolio, with different allocations based on investor risk profiles. High-risk portfolios maximize returns by 2% with a risk of 3.5%, while low-risk portfolios yield a return of 1.31% with a risk of 2.94%. This study is expected to serve as a reference for investors to make more measured investment decisions aligned with their risk preferences.